Cross-domain Identity Authentication in IoV - Zhang, Ming; Li, Yuhang; Guo, Yufan; Liao, Dan; Li, Hui; Li, Yujuan (Proceedings (International Conference on Communication Technology. Online), 2023)
To address the problems of identity forgery attack and low authentication efficiency, this paper proposes a cross-domain vehicle identity authentication algorithm based on the master-slave multi-chain, called CAMS. It utilizes the master-slave multi-chain to achieve cross-domain storage and sharing of vehicle data, thereby improving cross-domain authentication efficiency. Moreover, the CAMS algorithm introduces pseudonym generation and verification parameters in the cross-domain authentication process. It further verifies the vehicle identity before verifying the message, ensuring the anonymity of authentication identity and resisting the identity forgery attack. Finally, the simulation results show that the superior performance of the CAMS in terms of computational overhead and authentication efficiency.